Equity choices and long-term care policies in Europe : allocating resources and burdens in Austria, Italy, the Netherlands, and the United Kingdom /: allocating resources and burdens in Austria, Italy, the Netherlands, and the United Kingdom. (2017) - Unknown
No abstract available